Systematic review of the limited evidence for different surgical techniques at benign hysterectomy: A clinical guideline initiated by the Danish Health Authority. (September 2017) - Sloth, Sigurd Beier; Schroll, Jeppe Bennekou; Settnes, Annette; Gimbel, Helga; Rudnicki, Martin; Topsoee, Märta Fink; Joergensen, Annemette; Nortvig, Helene; Moeller, Charlotte
Abstract: Hysterectomy for benign gynecological conditions is a common operation that has developed extensively through the last 20 years. Methods and surgical techniques vary throughout the regions in Denmark as well as internationally. Consequently, the Danish Health Authority initiated a national clinical guideline on the subject based on a systematic review of the literature. A guideline panel of seven gynecologists formulated the clinical questions for the guideline. A search specialist performed the comprehensive literature search. The guideline panel reviewed the literature and rated the quality of evidence according to the Grading of Recommendations Assessment, Development and Evaluation (GRADE). Finally, the panel weighted the evidence and formulated the clinical recommendations. Based on the limited available literature and the corresponding quality of evidence according to GRADE, the guideline panel gave the following recommendations: ↓ Subtotal hysterectomy should only be preferred over total hysterectomy after careful consideration because there are documented disadvantages such as persistent cyclic vaginal bleeding (⊕ΟΟΟ). ↑ Consider vaginal hysterectomy rather than conventional laparoscopic hysterectomy for non-prolapsed uteri when feasible (⊕ΟΟΟ). ↓ Robot-assisted laparoscopic hysterectomy should only be preferred over conventional laparoscopic hysterectomy after careful consideration because the beneficial effect is uncertain and because of the longer operating time (⊕⊕ΟΟ). ↑ Consider concomitant bilateral salpingectomy at the time of hysterectomy if the procedure is not considered to increase the risk of complications significantly (⊕ΟΟΟ). ↑ Consider vaginal vault suspension to the cardinal and the uterosacral ligaments when performing hysterectomy for non-prolapsed uteri (⊕ΟΟΟ). Though supporting evidence is missing, the guideline panel emphasizes that it is good practice not to morcellate uteri with presumed fibroids inside the peritoneal cavity (√) . The recommendations serve as professional advice in specific clinical situations. The implementation of the guideline in Denmark will be monitored through the national Danish Hysterectomy and Hysteroscopy Database.